2014
DOI: 10.1108/ijchm-11-2012-0211
|View full text |Cite
|
Sign up to set email alerts
|

How do international tourists perceive hotel quality?

Abstract: Purpose – The aim of this paper is to identify tourists' perceptions of services provided by hotels in Antalya/Turkey and to explore hotel service quality dimensions. Specifically, the objectives are as follows: to identify the dimensions of hotel service quality, and to determine the relative impact of those dimensions on customer satisfaction levels, on customer value and on customers' intentions to recommend or revisit a hotel. Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…This supported the assertion that location including parking, convenience, accessibility and transportation from areas like airports and taxi services moreover affect guest satisfaction (Poon & Low, 2005). The relevance of these findings are clear given that Dortyol, Varinli and Kitapci (2014) likewise discovered that parking was important to hospitality guests while Lockyer (2005) equally found that location factors such as prices versus transport costs, needs and looks of the property were essential.…”
Section: Wwwccsenetorg/ijmssupporting
confidence: 70%
See 1 more Smart Citation
“…This supported the assertion that location including parking, convenience, accessibility and transportation from areas like airports and taxi services moreover affect guest satisfaction (Poon & Low, 2005). The relevance of these findings are clear given that Dortyol, Varinli and Kitapci (2014) likewise discovered that parking was important to hospitality guests while Lockyer (2005) equally found that location factors such as prices versus transport costs, needs and looks of the property were essential.…”
Section: Wwwccsenetorg/ijmssupporting
confidence: 70%
“…Choi and Chu (2000) already stated that "security factors such as responsible security personnel, loud reliable fire alarms and availability of safe boxes determined the satisfaction levels of guests in hotels". Dortyol et al (2014) likewise revealed that security and safety were important to these guests.…”
Section: Wwwccsenetorg/ijmsmentioning
confidence: 99%
“…their knowledge, skills, experience, understanding guests, friendly attitude toward guests, respect for guests, care, politeness, personal attention, tidiness etc. The second group represents the service process, which also affects: accuracy and efficiency in making a reservation, check-in speed, availability of a reserved room, accuracy in serving food in accordance with food ordered by a guest, correctness of all items in the bill, speed in the service provision, providing the service as promised, availability of information on the hotel services and their prices, solving problems, understanding guests' complaints (Akan, 1995;Akbaba, 2006;Dortyol et al, 2014;Juwaher, 2004;Oh, 1999).…”
Section: Intangible Elements Of the Hotel Servicementioning
confidence: 99%
“…The responsiveness of staff and the high quality of services were the attractive factors in consideration of outsourced BOM services. Room quality and services can enhance the role of the hotel and lead to increases in the hotel's room rates (Dortyol et al, 2014;Lu et al, 2015). The number of stars awarded to the hotel can be increased because of higherquality facilities and services.…”
Section: Outsource or Retain In-housementioning
confidence: 99%
“…There will be certain costs at the beginning, but the cost of maintaining the building can be controlled in the future (Henley et al, 2004). As such, hotel managers should not fear increases in capital allocation when it comes to upgrading the amenities of their hotels because the increased investment brings increased revenue (Dortyol et al, 2014). Most of the hotel managers were more interested in the speed and quality of outsourced BOM services rather than the cost.…”
Section: Outsource or Retain In-housementioning
confidence: 99%